Gender dynamics in the relationship among student-teacher relationships, academic task engagement, academic task value, and positive developmental outcomes - Getahun Tadesse Abren; Reda Darge Negasi; Amare Sahle Abebe (PLoS ONE, 2025)
This study examines gender differences in the direct and indirect relationships among student-teacher relationships, academic task engagement, perceived academic task value, and positive developmental outcomes among secondary school students. A correlational research design was used, and a cross-sectional survey was conducted with 500 students from grades 9 and 10 across five selected secondary schools. Multi-stage sampling technique employed to select participants. The study utilized Multi-Group Structural Equation Modeling (MGSEM) to examine gender difference. The results indicate that the student-teacher relationship and students’ perceived academic task value were associated with 40.3% of the variance in cognitive engagement among male students (R 2 = 0.403), while they explain 31.9% of the variance for female students (R 2 = 0.319). Regarding affective engagement, these factors were associated with 15.0% of the variance for males (R 2 = 0.150) and 12.6% for females (R 2 = 0.126). In terms of behavioral engagement, the model explains 26.4% of the variance for males (R 2 = 0.264) and 32.8% for females (R 2 = 0.328). Furthermore, the model were associated with 52.3% of the variance in positive development outcomes for male (R 2 = 0.523) and 54.9% for female (R 2 = 0.549). These findings underscore the necessity for gender-sensitive educational strategies that strengthen student-teacher relationships and tailor engagement approaches to promote positive developmental outcomes for both genders. Specifically, educators should focus on fostering supportive environments that recognize the unique needs of male and female students, thereby promoting higher levels of academic task engagement and positive developmental outcomes.